The great Atlantic Sargassum belt: Atmospheric-oceanic drivers, impacts, and management challenges in the Caribbean Sea - Rafael Méndez-Tejeda; José J. Hernández Ayala (Journal of Marine Studies, 2026)
In recent years, the coasts of the Caribbean, West Africa, and the Gulf of Mexico have faced a massive influx of pelagic Sargassum (Sargassum natans and S. fluitans), driven by climatic and oceanographic changes. These algae, once confined to the Sargasso Sea, now proliferate in a new source region: the Greater Atlantic Sargassum Belt (GASB), fed by river nutrients from the Amazon and Orinoco, equatorial upwellings, Saharan dust, and a small contribution from the Gulf of Guinea transported by trade winds. This alga is transported to the Caribbean by key currents such as the North Equatorial Current, the Caribbean Current, and the Gulf of Mexico Loop Current. These combine with climate patterns such as the North Atlantic Subtropical High (NASH), the North Atlantic Oscillation (NAO), and the Atlantic El Niño mode, which affect the routes and intensity of the blooms. Peaks occur between April and September, with critical years such as 2015, 2018, and 2025, when more than 33.5 million metric tons were estimated. Although satellite monitoring has improved, challenges remain, such as low resolution in turbid waters and the lack of models that integrate physical, chemical, and biological variables. Given the scale of this phenomenon, stronger regional cooperation between governments and the community at large is needed, along with effective early warning systems. This paper attempts to analyze some of the most relevant studies on the mechanisms of Sargassum transport to the Caribbean, providing scientific insights into evidence-based management.